2020
DOI: 10.1080/15592294.2020.1809853
|View full text |Cite
|
Sign up to set email alerts
|

Music-listening regulates human microRNA expression

Abstract: Music-listening and performance have been shown to affect human gene expression. In order to further elucidate the biological basis of the effects of music on the human body, we studied the effects of music-listening on gene regulation by sequencing microRNAs of the listeners (Music Group) and their controls (Control Group) without music exposure. We identified upregulation of six microRNAs (hsa-miR-132-3p, hsa-miR-361-5p, hsa-miR-421, hsa-miR-23a-3p, hsa-miR-23b-3p, hsa-miR-25-3p) and downregulation of two m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 82 publications
1
26
0
Order By: Relevance
“…Hence, the authors put forward the hypothesis that the periodic rhythm lasting like a physiological cycle (20–30 s) might explain the neuroplastic and behavioral benefits from music listening. Further research is needed to explore this hypothesis [ 159 , 160 ].…”
Section: Boosting Endogenous Bdnf: Musicmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the authors put forward the hypothesis that the periodic rhythm lasting like a physiological cycle (20–30 s) might explain the neuroplastic and behavioral benefits from music listening. Further research is needed to explore this hypothesis [ 159 , 160 ].…”
Section: Boosting Endogenous Bdnf: Musicmentioning
confidence: 99%
“…Thus far, only two studies [ 137 , 161 ] have measured BDNF levels in humans after musical activities, compared with at least 29 studies showing BDNF modulation after sport practice (as reported by the meta-analysis dated back to 2015 [ 5 ]). On the other hand, genetic research demonstrates a relation between BDNF and music functions in humans with BDNF-related gene mutations associated with musical abilities [ 159 ], as well as increased BDNF microRNA transcription after a concert performance of professional ensemble musicians [ 162 ], or even simply after listening to 20 min of the violin concerto K. 216 by Mozart [ 160 ] (to note, these BDNF gene modulations were found in association with music functions, along with several other genes related to auditory system functions, affiliation, and neuronal development). Thus, future research is called for to better investigate this topic, and here we wish to provide some ideas that such research should pursue.…”
Section: Boosting Endogenous Bdnf: Musicmentioning
confidence: 99%
“…Of note, there is overlap between the results of microRNAs and those of genes differentially expressed; in particular, some of these genes are target of the miRNAs with differential expression, both regarding the conditions of music performance and listening to music. In this body of research, samples of peripheral whole blood were used, as its transcriptome is shared for more than 80% with other tissues, including the brain which is inaccessible [148][149][150][151]. It has been verified that, for professional musicians, a concert of two hours induces a differential expression of 73 genes, involving both upregulation (51 genes) and downregulation (22 genes) [127].…”
Section: The Effect Of Music On Gene Expression and Brain Activitymentioning
confidence: 99%
“…The cultural and epigenetic systems of heritage may thus provide the "missing" heritability of complex diseases that is currently the subject of much scientific discourse'. Although music-epigenetics is still a fairly undiscovered field, Brigati [51] pointed out that music is a highly transmissible cultural product and social epigenetics describe how communication and emotion -'prime hallmarks of music' -can be linked to a transmissible, biochemical change, and recent epigenetic studies [52] showed that music listening regulates human microRNA expression.…”
Section: Psyche To Cancermentioning
confidence: 99%
“…Taking Daoistic views of permanent changes, which also concern music and the psyche, into account and merge them with epigenetic considerations about the influence of music on gene expression, e.g. that listening to music regulates human microRNA-expression [56], there are good reasons to assume complex dynamic functions of music in oncology and to suggest related translational research. In this context we also draw attention to the fact that miR-132, which belongs to the 'music-sensitive' microRNAs, plays a critical role in regulating TAU protein levels, hence its importance for preventing TAU protein aggregation in Alzheimer's disease.…”
Section: Multimodal Systemsmentioning
confidence: 99%